DETERMINAN PENGANGGURAN TERSELUBUNG DI PROVINDI JAWA TIMUR - Ihza Syahniar Afif; Santoso, Dwi Budi (Journal of Development Economic and Social Studies, 2024)
This study aims to determine what factors influence underemployment in East Java Province. This study uses several variables such as age, education level, and training participation. The methods used are Linear Probability Model (LPM), Logit, and Probit. The focus of this research is how to reduce the probability of the workforce being trapped into underemployment. The results of this study indicate that the age factor has a positive and significant effect on underemployment where as age increases the probability of becoming underemployed also increases. Furthermore, the education factor shows negative results, the higher the level of education, the lower the probability of underemployment. Workers with an elementary school education level are most prone to being trapped into underemployment. Meanwhile, workers with university graduates have the lowest chance of becoming underemployed. The training participation factor shows that workers who attend training have a lower probability of becoming underemployed.